Real-world Biapenem vs. Meropenem in the treatment of severe community-acquired pneumonia in children: A propensity score matching analysis - Tao, Xuemei; Xu, Changjing; Zhong, Xiaoyan; Mou, Yao; Li, Jingwei; Yang, Xuping; Huang, Yilan (Frontiers in Pediatrics, 2022)
Objective: Biapenem has been poorly studied in children. To compare effectiveness and safety of biapenem and meropenem in the real world. Methods: We retrospectively evaluated 915 children with severe community-acquired pneumonia (SCAP) who were treated with biapenem or meropenem from August 2018 to June 2022. Propensity-score matching analysis was performed with a 1:1 ratio to reduce the real-life baseline difference between the two groups. Results: After propensity score matching, 416 patients were included in the analysis (biapenem:meropenem=1:1). For the biapenem group and meropenem group, the effective rates were 90.4% and 90.9%, respectively (p=1.0) and the incidence of adverse reactions were 7.7% and 7.2%%, respectively (p=1.0). There were no statistical differences between the two groups. Conclusion: Biapenem is as effective and safe as meropenem in the treatment of children with SCAP.